Dual guidewire balloon antegrade fenestration and re‐entry technique for coronary chronic total occlusions percutaneous coronary interventions. Issue 4 (12th July 2022) - Galassi, Alfredo R.; Vadalà, Giuseppe; Testa, Gabriella; Puglisi, Sebastiano; Sucato, Vincenzo; Diana, Davide; Giunta, Rocco; Novo, Giuseppina
Abstract: Objectives: To describe the experience of coronary chronic total occlusions (CTOs) percutaneous coronary interventions (PCI) using antegrade fenestration and re‐entry (AFR) technique with a dedicated dual guidewire balloon (DGB). Background: Antegrade dissection and re‐entry (ADR) techniques has been emphasized in recent worldwide CTO consensus documents. We investigated the feasibility and safety of DGB as a dedicated device to perform guidewire‐based AFR. Methods and Results: Fourteen consecutive patients with complex CTO (J‐CTO score: 3.1 ± 0.9) underwent DGB‐AFR in the years 2020–2021. DGB‐AFR consists in advancing the DGB over a guidewire that reached the vessel distal to the CTO in an extra plaque fashion, inflating/deflating the DGB to create fenestration between subintimal space and the true lumen and advancing a proximal re‐entry guidewire through fenestration in the true lumen. DGB‐AFR alone was successful in 10 of 14 (71%) cases, a rescue wire‐based ADR was needed in two cases for re‐entry into the true lumen with a total success rate in 12 of 14 (86%) cases. Among all DGB‐AFR cases, four (28%) were performed as a first‐line strategy while the remaining 10 (71%) cases were performed as a bail‐out strategy after failure of other antegrade crossings for 30 min of procedural time. No DGB‐related complications were observed. Conclusions: DGB‐AFR is a user‐friendly reliable strategy for the treatment of many CTO lesions. It can be used as bail‐out after failure of conventional antegrade wiring techniques, achieving high procedural success rate and low occurrence of procedural adverse events.